1998
DOI: 10.1111/j.1439-0434.1998.tb04677.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saline Environment on Yield and Smut Disease Severity of Different Corn Genotypes (Zea mays L.)

Abstract: The effects of salitie irrigation water on growth, yield, smut index and leaf CI content were investigated under field conditions. The plants were grown in 1994 and 1995 and artificially infected with U. maydis-spore-suspension at V^ and V,o leaf stages. The severity was rated on a 1-9 scale, whenever the symptotns appeared. The results showed that superior growth, greater yield performance, associated with lower smut incidence and leaf Cl contents were generally observed on Taba than its counterparts. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…It is thus of great importance to examine plant responses to combinations of abiotic and biotic stress factors, important variables that are relevant to crop yields (Soliman and Kostandi, 1998; Kissoudis et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus of great importance to examine plant responses to combinations of abiotic and biotic stress factors, important variables that are relevant to crop yields (Soliman and Kostandi, 1998; Kissoudis et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Field crops are grown under the same variable conditions; however, as they are bred and selected under relatively controlled conditions, several trade-offs might have been overlooked that can result in negative interactions under field conditions ( Brown and Rant, 2013 ; Hückelhoven et al , 2013 ; McGrann et al , 2014 ). It is thus of great importance to examine plant responses to combinations of abiotic and biotic stress factors, important variables that are relevant to crop yields ( Soliman and Kostandi, 1998 ; Kissoudis et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Observations of the effects of abiotic stress on foliar pathogens are on the other hand mixed, with studies reporting either enhanced (Achuo et al 2006;Wiese et al 2004), or decreased resistance (Roubtsova and Bostock 2009;Sanogo 2004). Abiotic stress severity can affect responses to abiotic and biotic stress combinations (Soliman and Kostandi 1998), and therefore the outcome of the interaction may be dependent on the specific environmental conditions under which it occurs.…”
Section: Introductionmentioning
confidence: 99%
“…and Cl -up to levels that were toxic for the fungus (evidenced by the increased fungal growth under salt stress). The severity of the stress can influence the magnitude of impact of another stress (Soliman and Kostandi 1998). Preliminary results in our laboratory indicated that the impact of salt stress on PM growth may depend on the severity of the applied stress (unpublished results).…”
Section: S Habrochaites Lyc4 Introgression Contribute To Partial Resmentioning
confidence: 99%
“…Many studies concluded that exposure of plants to salinity stress can significantly increase the susceptibility of tomato to root knot nematode (Endongali and Ferris, 1982;Maggenti and Hardan, 1973), and to increase the susceptibility of citrus and chrysanthemum to Phytophthora root rots (Blaker and MacDonald, 1986;MacDonald, 1984;Swiecki and MacDonald, 1988). Soliman and Kostandi (1998) showed that maize had varying susceptibility to smut disease caused by Ustilago maydis under different concentrations of NaCl. The low levels of salinity (25-50mM) could increase the severity of phytophthora root rot of tomato with high Na:Ca ratios (10:1) (Bouchibi et al, 1990); Phytophthora (Roubtsova and Bostock 2009;Sanogo, 2004), F. oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%